Situs Sendang Duwur di Kabupaten Lamongan Jawa Timur - Izza Ainun Nurkholishoh; Wiwin Hartanto; Rully Putri Nirmala Puji (LP4MK STKIP PGRI Lubuklinggau, 2020)
Abstract Sunan Sendang Duwur was one of the mayors whose role was equated with Walisongo in broadcasting Islam in Java. Sunan Sendang preaches culturally by acculturating the culture that has tradition in Sendang Duwur Village and internalizing it with Islamic values. His teachings about